Donepezil, anti-Alzheimer's disease drug, prevents cardiac rupture during acute phase of myocardial infarction in mice. - Mikihiko Arikawa; Yoshihiko Kakinuma; Takemi Handa; Fumiyasu Yamasaki; Takayuki Sato (PLoS ONE, 2011)
BACKGROUND: We have previously demonstrated that the chronic intervention in the cholinergic system by donepezil, an acetylcholinesterase inhibitor, plays a beneficial role in suppressing long-term cardiac remodeling after myocardial infarction (MI). In comparison with such a chronic effect, however, the acute effect of donepezil during an acute phase of MI remains unclear. Noticing recent findings of a cholinergic mechanism for anti-inflammatory actions, we tested the hypothesis that donepezil attenuates an acute inflammatory tissue injury following MI. METHODS AND RESULTS: In isolated and activated macrophages, donepezil significantly reduced intra- and extracellular matrix metalloproteinase-9 (MMP-9). In mice with MI, despite the comparable values of heart rate and blood pressure, the donepezil-treated group showed a significantly lower incidence of cardiac rupture than the untreated group during the acute phase of MI. Immunohistochemistry revealed that MMP-9 was localized at the infarct area where a large number of inflammatory cells including macrophages infiltrated, and the expression and the enzymatic activity of MMP-9 at the left ventricular infarct area was significantly reduced in the donepezil-treated group. CONCLUSION: The present study suggests that donepezil inhibits the MMP-9-related acute inflammatory tissue injury in the infarcted myocardium, thereby reduces the risk of left ventricular free wall rupture during the acute phase of MI.